Oxidative stress, metabolic and histopathological alterations in mussels exposed to remediated seawater by GO-PEI after contamination with mercury - Coppola, Francesca (2020)
The modern technology brought new engineering materials (e.g. nanostructured materials) with advantageous characteristics such as a high capacity to decontaminate water from pollutants (for example metal(loid)s). Among those innovative materials the synthesis of nanostructured materials (NSMs) based on graphene as graphene oxide (GO) functionalized with polyethyleneimine (GO-PEI) had a great success due to their metal removal capacity from water. However, research dedicated to environmental risks related to the application of these materials is still non-existent. To evaluate the impacts of such potential stressors, benthic species can be a good model as they are affected by several environmental constraints. Particularly, the mussel Mytilus galloprovincialis has been identified by several authors as a bioindicator that responds quickly to environmental disturbances, with a wide spatial distribution and economic relevance. Thus, the present study aimed to evaluate the impacts caused in M. galloprovincialis by seawater previously contaminated by Hg and decontaminated using GO-PEI. For this, histopathological and biochemical alterations were examined. This study demonstrated that mussels exposed to the contaminant (Hg), the decontaminant (GO-PEI) and the combination of both (Hg + GO-PEI) presented an increment of histopathological, oxidative stress and metabolic alterations if compared to organisms under remediated seawater and control conditions The present findings highlight the possibility to remediate seawater with nanoparticles for environmental safety purposes.